Animating Sympathetic Feelings. An Analysis of the Nature of Sympathy in the Accounts of David Hume’s Treatise - Borza, Natalia (Conatus - Journal of Philosophy, 2019)
Sympathy is a powerful principle in human nature, which can change our passions, sentiments and ways of thinking. For the 18th century Scottish philosopher David Hume, sympathy is a working mechanism accountable for a wide range of communication: the ways of interacting with the others’ affections, emotions, sentiments, inclinations, ways of thinking and even opinions. The present paper intends to find a systematic reading of Hume’s Treatise of Human Nature (1739) from the point of view of what the mechanism of sympathetic communication implies in terms of strengthening our action of understanding, of being sensitive to, and vicariously experiencing the feelings, thoughts, and experience of others. Hume’s description of the sympathetic mechanism appears to suggest that sympathetic passions come upon us purely by natural means in a passive manner, without the active use of any of our faculties. Consequently, scholarly attention is drawn to the mechanistic character of the sympathetic process; its automatic nature is emphasized to such an extent that some experts even find it to be completely void of any reflective process. The current study investigates to what extent the sympathetic process can actively be modified and in what manner sympathetic feelings can be generated as described in Hume’s system of emotions. The paper identifies at which points the otherwise mechanically and passively operating process of sympathetic feelings is open to be modified by actively altering or strengthening certain skeletal points of the mechanism. I argue that the alterations can be initiated by the person who receives the sympathetic feelings and also by the person whose passions are transmitted, moreover even by a third party. In a seemingly mechanic model, there is room for altering or at least amplifying one’s sympathetic feelings.